2023
DOI: 10.3389/fnut.2023.1197382
|View full text |Cite
|
Sign up to set email alerts
|

Production, identification, in silico analysis, and cytoprotection on H2O2-induced HUVECs of novel angiotensin-I-converting enzyme inhibitory peptides from Skipjack tuna roes

Abstract: BackgroundExceeding 50% tuna catches are regarded as byproducts in the production of cans. Given the high amount of tuna byproducts and their environmental effects induced by disposal and elimination, the valorization of nutritional ingredients from these by-products receives increasing attention.ObjectiveThis study was to identify the angiotensin-I-converting enzyme (ACE) inhibitory (ACEi) peptides from roe hydrolysate of Skipjack tuna (Katsuwonus pelamis) and evaluate their protection functions on H2O2-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Antihypertensive peptides derived from food proteins exhibit the capacity to reduce blood pressure in hypertensive patients (Zhang et al, 2018a) inhibitory peptides Ala-Ser-Pro-Tyr-Ala-Phe-Gly-Leu with IC 50 value of 1.08 × 10 −7 mol L −1 from mushrooms by sulfuric acid hydrolysis and indicated that mushrooms could be exploited as multifunctional ingredients for drugs or functional foods against osteoarthritis and hypertension (Zhang et al, 2017). In addition, peptides with ACE inhibitory activity were also extracted from marine food sources, such as Skipjack tuna muscles and roes as well as Mytilus edulis demonstrating their potential as functional foods against hypertension and cardiovascular diseases (Suo et al, 2022a;Zheng et al, 2022;Zhu et al, 2023).…”
Section: Antihypertensive Peptidesmentioning
confidence: 99%
“…Antihypertensive peptides derived from food proteins exhibit the capacity to reduce blood pressure in hypertensive patients (Zhang et al, 2018a) inhibitory peptides Ala-Ser-Pro-Tyr-Ala-Phe-Gly-Leu with IC 50 value of 1.08 × 10 −7 mol L −1 from mushrooms by sulfuric acid hydrolysis and indicated that mushrooms could be exploited as multifunctional ingredients for drugs or functional foods against osteoarthritis and hypertension (Zhang et al, 2017). In addition, peptides with ACE inhibitory activity were also extracted from marine food sources, such as Skipjack tuna muscles and roes as well as Mytilus edulis demonstrating their potential as functional foods against hypertension and cardiovascular diseases (Suo et al, 2022a;Zheng et al, 2022;Zhu et al, 2023).…”
Section: Antihypertensive Peptidesmentioning
confidence: 99%
“…Four peptides among the fifteen extracted peptides showed remarkable ACE-inhibitory activity. [79] Chinese sturgeon (Acipenser sinensis)…”
Section: Skipjack Tuna (Katsuwonus Pelamis)mentioning
confidence: 99%
“…RP-HPLC is an extremely efficient technology for isolating ACEi peptides according to their RT, and the RT of separated ACEi peptides can be modulated by adjusting the ratio of polar solvent (such as trifluoroacetic acid (TFA), methanol, ethyl alcohol and acetonitrile) in the mobile phase [30,32,64]. Therefore, ACEi peptides have been separated using RP-HPLC from protein hydrolysates of T. bimaculatus [28], R. philippinarum [67], Skipjack tuna roes [31], M. edulis [30], Kuruma shrimp [66], pearl oyster [68], Pyropia pseudolinearis [69], squilla [39], hybrid groupers [41], Arthrospira platensis [70], etc.…”
Section: Sequences and Mw Determination Of Mhp6 Mhp7 And Mhp9mentioning
confidence: 99%
“…[29,30]. However, the World Health Organization (WHO) reports that the number of people with hypertension will increase from 1.28 billion to 1.56 billion by 2030 [31]. ACE can modify angiotensin (Ang) I to active Ang II to upregulate blood pressure by inactivating the vasodilator bradykinin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation